TANGGUNGJAWAB DEVELOPER ATAS KERUGIAN KONSUMEN AKIBAT WANPRESTASI DALAM PERJANJIAN JUAL BELI RUMAH - Tejakusuma, Jonathan; Subekti, Subekti; Handayati, Nur; Prawesthi, Wahyu (Gapenas Publisher, 2025)
A sale and purchase agreement is generally a consensual agreement, as it binds the parties upon their agreement on the essential and incidental elements of the agreement. A house sale and purchase agreement will give rise to the rights and obligations of each party and will be set out in a house sale and purchase agreement deed that will bind both parties to the agreement. The parties to the agreement are required to fulfil their respective obligations. If one party is unable or fails to perform its obligations, the other party may claim damages for the breach. The main issues are the developer's liability for consumer losses due to default in the house sale and purchase agreement and the form of legal protection for consumer losses due to developer default in the house sale and purchase agreement. The approach used in this study is a normative legal approach. The normative juridical approach uses legislation, examining all laws and regulations related to the legal issues being addressed. The conceptual approach departs from the views and doctrines that have developed in legal science. The results of the research on developer liability for consumer losses due to breach of contract in house sale and purchase agreements show that the form of legal liability that can be imposed on developers for breach of contract can cover several aspects, namely civil and criminal, depending on the problem or case involving the developer's breach of contract with the consumer. Developers have a responsibility that must be fulfilled.).